Learning The Human Digestive System Through The Use of Problem-Based Learning: Efforts to Improve Student Activities and Outcomes - Aristaningsih, Arfi; Erari, Semuel Sander; Rumalolas, Nuryanti; Rahman, Sari Rahayu; Nasir, Nur Indah Ririn Fitriani; Nunaki, Jan Hendriek; Damopolii, Insar (Jurnal Report of Biological Education, 2025)
Background: Student activity and their achievement in science teaching in junior high school are still declining, which causes them to fail in learning. Methods: . This study employs problem-based learning (PBL) to enhance student engagement and learning outcomes, particularly regarding the material on the digestive system. A total of 30 grade VIII students from one of the Islamic junior high schools in the Manokwari city area participated in the teaching. The study began with planning learning, actions, and observations, and ended with reflection in each cycle. We conducted the study in two cycles. Results: The findings of the study indicated that student activity increased by 5%, where in cycle I it was 95% and in cycle II it reached 100%. From cycle I to II, the percentage of student learning outcomes increased by 43.34%. Conclusion: Based on the results of the study, it can be concluded that the implementation of PBL can enhance the learning outcomes and activities of students in class VIIIA of junior high school regarding the human digestive system.